2022
DOI: 10.1016/j.chb.2021.107175
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 infodemic at your fingertips. Reciprocal relationships between COVID-19 information FOMO, bedtime smartphone news engagement, and daytime tiredness over time

Abstract: Considering that insufficient sleep has long been regarded as a significant public health challenge, the COVID-19 pandemic and its co-evolving infodemic have further aggravated many people's sleep health. People's engagement with pandemic-related news, particularly given that many people are now permanently online via smartphones, has been identified as a critical factor for sleep health, such that public health authorities have recommended limited news exposure. This two-wave panel survey, conducted with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…In problematic smartphone use model, FoMO partially mediated the relationship between perceived COVID-19-related restrictions and problematic smartphone use. The results supported that perceived COVID-19-related restrictions is positively associated with FoMO, FoMO mediates the association between perceived COVID-19-related restrictions and problematic smartphone use among college students, and indicated that FoMO had an important influence on problematic smartphone use during the epidemic closure, which is consistent with previous research ( 17 ). According to self-determination theory, epidemic closure disrupts the rhythm of students' lives, and college students are fundamentally different from junior and senior high school students in that junior and senior high school students are subject to certain restrictions in their daily lives even if they do not undergo epidemic closure ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In problematic smartphone use model, FoMO partially mediated the relationship between perceived COVID-19-related restrictions and problematic smartphone use. The results supported that perceived COVID-19-related restrictions is positively associated with FoMO, FoMO mediates the association between perceived COVID-19-related restrictions and problematic smartphone use among college students, and indicated that FoMO had an important influence on problematic smartphone use during the epidemic closure, which is consistent with previous research ( 17 ). According to self-determination theory, epidemic closure disrupts the rhythm of students' lives, and college students are fundamentally different from junior and senior high school students in that junior and senior high school students are subject to certain restrictions in their daily lives even if they do not undergo epidemic closure ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…COVID-19-related restrictions break down people's autonomy, competence and relatedness, and spatial and social restrictions compromise these three basic needs, creating FoMO. In addition, a study by Koban confirmed that an increase in epidemic-related FoMO can affect a person's level of mental health and contribute to daytime fatigue ( 17 ). Thus, FoMO may mediate the relationship between COVID-19-related restrictions and problematic smartphone use or levels of mental health.…”
Section: Introductionmentioning
confidence: 97%
“…The uncertain and rapidly changing nature of the pandemic, coupled with shelter-in-place and work-from-home orders in the first year of the pandemic, increased access to and demand for information about COVID-19 [ 1 , 2 ]. News consumption increased across multiple forms of media, including increases in television news viewership, daily visits to news websites, and the use of mobile phones to monitor pandemic updates [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first kind of pathway is feeling extremely scared → prolonged smartphone use → depression, indicating that feeling extremely scared could be associated with depression through the mediating role of prolonged smartphone use. Participants feeling extremely scared may hope to get as much information about the pandemic as possible or seek alleviation of their fear and distress through online activities, such as watching TV, gaming, shopping, and communicating through smartphones (67)(68)(69). Volpe et al observed a rise in problematic internet use, social media addiction, and problematic video gaming during COVID-19.…”
Section: Discussionmentioning
confidence: 99%